Cyperus sulcinux C. B. Clarke. A New Record from Kumaon Himalaya - Rao, A. S.; Murti, S. K. (Indian Forester, 1980)
Cyperus sulcinux C.B.CI., a genarally wide-spread species, but rare and confined to small pockets within this range of distribution, and hitherte unknown from the Kumaon Himalaya, is here recorded for the first time and briefly described.